The use of formal language as a strong sign of verbal autistic children in diglossic communities: The case of Arabic - Francis, Konstantinos; Alshammari, Nasser; Alsulaihim, Nailah; Aboukhamseen, Suja; El Dardiri, Mohammad; AlRashidi, Fawzeiah; Ridha, Hashem Almutaz; AL‐Hassan, Mada; Terzi, Arhonto (Autism research, 2024)
The current study aimed to investigate whether the use of formal language (Modern Standard Arabic [MSA]) by young children in diglossic Arab communities offers diagnostic insights, especially for verbal autistic children and to further explore this phenomenon. We used a cohort study design, with 4–6‐year‐old fluent first language Arabic‐speaking children attending Arabic Kindergartens in two representative Kuwait governates. Reported cases for MSA use were assessed via a computer‐based structured language test and corroborated cases were further assessed for exposure to sources of MSA, verbal IQ, temperamental characteristics, and autism spectrum disorder (ASD). Four children from the same class without developmental difficulties were selected for each MSA user as control group. The frequency of MSA use among verbal pre‐schoolers was 0.46%. Use of MSA did not correlate with parents' education, amount of exposure to MSA, verbal IQ, but with severity of ASD. Predicted probability of ASD in the presence of MSA was 0.86. Executive functions of ASD‐MSA users were similar to those of the control group and significantly higher than unselected autistic peers in the literature. The use of MSA has the potential to serve as a strong sign for the diagnosis of verbal autistic children, often missed or delayed in being diagnosed. We also discuss strategies via which language is acquired in ASD. Lay Summary Arabic is a language known to come in two clearly distinct varieties: one used in most everyday situations (colloquial) and another (formal) used in formal settings, such as school books and teaching, religious settings, video games, Arab cartoons, TV news, and documentaries. We noticed that children with autism spectrum disorder (ASD) may use the formal version in everyday interactions, which is highly uncommon. Our study aimed to see if this uncommon use of formal language could lead to early detection of ASD. We examined 4–6‐year‐old children in Kuwaiti public kindergartens, checking for signs of ASD in those children who used formal language in their daily chats. Out of 5314 children, only a few (0.46%) used formal language in this context, and most of them (86%) were diagnosed for ASD. This odd language use wasn't linked to children's intelligence, to their parents' education level, or to how much they watched TV or used electronics. Instead, it correlated with the social and communication challenges of ASD. Our findings suggest that noticing such language differences can help identify verbal autistic children who might otherwise be missed in diagnosis. This can lead to earlier support, but also offer insights into how these children learn language differently, hence, potentially improve intervention.